METHODOLOGY FOR DEVELOPING AND IMPROVING THE TECHNICAL TRAINING OF 13-14 YOUNG FOOTBALL PLAYERS. - Ergasheva Muxlisa G‘ulomjon qizi; Otaqulov Murodjon Nizomjon o‘g‘li (Ustozlar uchun, 2025)
In football, ball handling technique is usually considered as a means of playing the game and, to some extent, as an external form of movement of the player. There is an opinion that everything that is done with a soccer ball during training is useful. Issues related to the technique of ball handling by football players are described.